2017
DOI: 10.21608/eos.2017.78353
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of different beverages on the mechanical properties of orthodontic arch wires

Abstract: Purpose: This study was conducted to evaluate the effect of different beverages on surface microhardness, modulus of elasticity and flexural strength of orthodontic archwires. Materials and Methods: Four orthodontic archwires (stainless steel, NiTi, copper NiTi and Teflon-coated NiTi) were used. They were immersed in three different solutions (Artificial saliva, tea and Coca Cola) for four weeks. For mechanical properties assessment, the specimens were classified mainly into four groups (90 specimens each) acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…In the present study, the control group always exhibited better mechanical properties. These ndings are in agreement with similar reports in previous studies when NiTi archwires were exposed to various drinks, mouthwashes, gastric juices or even saliva [9][10][11][12][13][14][15]. Hafez evaluated the effect of different solutions (arti cial saliva, tea, and Coca-Cola) on modulus of elasticity and exural strength of orthodontic archwires.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, the control group always exhibited better mechanical properties. These ndings are in agreement with similar reports in previous studies when NiTi archwires were exposed to various drinks, mouthwashes, gastric juices or even saliva [9][10][11][12][13][14][15]. Hafez evaluated the effect of different solutions (arti cial saliva, tea, and Coca-Cola) on modulus of elasticity and exural strength of orthodontic archwires.…”
Section: Discussionsupporting
confidence: 91%
“…They reported a signi cant reduction in the modulus of elasticity of all archwire specimens after their immersion. It was concluded that Tea and Coca-Cola could potentially change the mechanical properties of orthodontic archwires leading to prolonged orthodontic treatment [9].…”
Section: Discussionmentioning
confidence: 99%
“…Acidic foods and drinks not only damage enamel but also shorten the lifetime of dental repairs [ 5 ]. These drinks weaken the surface hardness, surface integrity, and solubility of the substances and lead to metal corrosion [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%